The Potential Efficiency of Bacillus subtilis AIK to Remove Nickel from Aqueous Solutions - Al-Muttairi, Ali K.; Al-Mayaly, Ithar K. (Iraqi Journal of Science, 2023)
In this study a new strain of mesophilic Bacillus subtilis AIK, recorded for the first time in Iraq, was used to remove nickel (Ni) from aqueous solutions. The factors that affect bioremediation include temperature, pH value and metal concentrations. The results showed that the highest removal efficiency (R%) was 54, 52 and 48% at 25⁰C and pH of 5, 7 and 9, and with 10 ppm Ni concentration respectively. Whereas the highest R% recorded was 47, 45 and 52% at 30⁰C and of pH 5, 7, and 9 with 1 ppm Ni concentration respectively. On the other hand, the highest R% at 40⁰C was 49, 46, 42 % at pH 5, 7 and 9, with 5, 10 and 10 ppm Ni concentrations respectively. The results also showed that the optimum pH value for Ni removal at both 25 and 40⁰Cwas 5, while at 30⁰C it was 9. The optimum temperature was kept at 25⁰C. In general, B. subtilis AIK showed an admissible capacity to remove Ni from aqueous solutions.